Relationship between Blood Urea Level and Left Ventricular Ejection Fraction (LVEF) in Patients with ST-Elevation Myocardial Infarction - Dewi U. Djafar; Marshell Luntungan; Agnes L. Panda; Steven Setiawan (e-CliniC, 2022)
Abstract: Lower left ventricular ejection fraction (LVEF) is associated with greater mortality among patients with ST-elevation myocardial infarction (STEMI). Renal dysfunction is considered to worsen the prognosis of STEMI patients. This study aimed to determine the correlation between blood urea level and left ventricular ejection fraction in patients with STEMI. This was a descriptive and analytical study using the Spearman’s rho test. Correlation was significant at the 0.05 level.  Data were collected from iSTEMI Registry database of patients admitted in Prof. Dr. R. D. Kandou General Hospital from October 3rd, 2018 to July 28th, 2019. The results obtained 172 STEMI patients with the mean age of 59.47±9.92 years old, and most were male (77.3%). The median blood urea level was 37 mg/dL (IQR 16) whereas a mean ejection fraction was 46.43%±10.43. The Spearman’s rho test showed that higher blood urea level was significantly associated with lower left ventricular ejection fraction (p=0.01; r=-0.241). In conclusion, higher blood urea level is associated with decreased left ventricular ejection fraction in patients with ST-elevation myocardial infarctionKeywords: blood urea level; left ventricular ejection fraction; STEMI Abstrak: Fraksi ejeksi ventrikel kiri yang menurun dikaitkan dengan tingginya mortalitas pada penderita infark miokard akut (IMA) dengan elevasi segmen ST (STEMI). Disfungsi renal diketahui memperburuk prognosis penderita IMA-EST. Penelitian ini bertujuan untuk meng-evaluasi korelasi antara kadar ureum darah dengan fraksi ejeksi ventrikel kiri pada penderita STEMI. Jenis penelitian ialah deskriptif analitik menggunakan data registri iSTEMI penderita STEMI yang dirawat di RSUP Prof. Dr. R. D. Kandou dari 3 Oktober 2018 hingga 28 Juli 2019. Penyajian deskriptif dan korelasi bivariat Spearman rho dilakukan untuk menganalisis hubungan kadar ureum darah dan fraksi ejeksi ventrikel kiri. Hasil penelitian mendapatkan 172 penderita STEMI dengan usia rerata 59,47±9,92 tahun; mayoritas ialah laki-laki (77,3%); median kadar urea darah ialah 37 mg/dL (rentang interkuartil 16); dan rerata fraksi ejeksi ialah 46,43%±10,43. Hasil uji Spearman rho menunjukkan bahwa peningkatan kadar urea darah secara bermakna berhubungan dengan fraksi ejeksi ventrikel kiri yang menurun (p=0,01; r=-0,241). Simpulan penelitian ini ialah peningkatan kadar urea darah berhubungan dengan menurunnya fraksi ejeksi ventrikel kiri pada penderita STEMI.Kata kunci: kadar urea darah; fraksi ejeksi ventrikel kiri; STEMI